Efektivitas program keluarga berencana dalam menekan laju pertumbuhan penduduk di Kota Pekanbaru - Rosa Pasrah S.D; Tri Sukirno Putro; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in the city of Pekanbaru on the grounds that as the capital city of Pekanbaru Riau, Pekanbaru City and has a higher population growth than the other regencies / cities in Riau Province. The purpose of this study is to see how much influence family planning programs in reducing the rate of population growth in the city of Pekanbaru. Methods of data analysis used in this study is descriptive method with qualitative approach. The data analysis technique used in this study is the analysis of qualitative data that outlines and interpret the data obtained in the field of the key informants (key informants). In determining the key informant authors choose key informants based characteristics to suit the purposes of research or thought to have information relevant to the subject matter of research. Key informants in this study is the Head of Control Family Planning and Family Welfare BPPMKB Pekanbaru City. This is because the key informant knows and has basic information required in this research. From these results it is concluded that the family planning program in the city of Pekanbaru can be said to demonstrate the success of an effective yet it remains characterized by the increases in population and birth rate. The population of Pekanbaru city in 2011 amounted to 937 939 inhabitants, in 2012 increased to 964 558 people, or an increase of 2.83% on average beat the national population growth of less than 2%. The number of births in 2012 also increased by 1,248 from 18,236 souls soul into soul 19 484, an increase of 6.4% from the previous year.Keywords: Effectiveness, Family Planning, Population Growth